Liquidity buffers and open-end investment funds: Containing outflows and reducing fire sales - Lennart Dekker; Luis Molestina Vivar; Michael Wedow; Christian Weistroffer (European Central Bank (ECB), 2023)
Using a sample of open-end corporate bond funds domiciled in the euro area, we exploit the COVID-19 market turmoil in March 2020 to examine two channels through which liquidity buffers can reduce procyclicality in the investment fund sector. First, we find that liquidity buffers reduced outflows during March 2020 only to a limited extent. Second, we find that funds entering the crisis with higher liquidity buffers were less likely to involve in cash hoarding and more likely to use cash buffers to meet outflows. Our results suggest that higher liquidity buffers can reduce procyclicality primarily through supporting the liquidity management strategies employed by fund managers.
Keywords: G01; G11; G23; 330; corporate bond funds; investor redemptions; liquidity management; COVID-19 pandemic